2022
DOI: 10.1038/s41467-022-33307-8
|View full text |Cite
|
Sign up to set email alerts
|

β-arrestin1 and 2 exhibit distinct phosphorylation-dependent conformations when coupling to the same GPCR in living cells

Abstract: Abstractβ-arrestins mediate regulatory processes for over 800 different G protein-coupled receptors (GPCRs) by adopting specific conformations that result from the geometry of the GPCR–β-arrestin complex. However, whether β-arrestin1 and 2 respond differently for binding to the same GPCR is still unknown. Employing GRK knockout cells and β-arrestins lacking the finger-loop-region, we show that the two isoforms prefer to associate with the active parathyroid hormone 1 receptor (PTH1R) in different complex confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 60 publications
3
36
0
Order By: Relevance
“…These data led to the conclusion that phosphorylation of the ICL3 promotes a conformation of β-arrestin that selectively targets the ERK1/2 signaling pathway. Similar results were recently found by Haider et al (2022) who showed that different phosphorylation sites on the parathyroid hormone 1 receptor were involved in regulating ERK1/2 activation and receptor internalization, which are both β-arrestin-mediated processes [ 52 ].…”
Section: Discussionsupporting
confidence: 88%
“…These data led to the conclusion that phosphorylation of the ICL3 promotes a conformation of β-arrestin that selectively targets the ERK1/2 signaling pathway. Similar results were recently found by Haider et al (2022) who showed that different phosphorylation sites on the parathyroid hormone 1 receptor were involved in regulating ERK1/2 activation and receptor internalization, which are both β-arrestin-mediated processes [ 52 ].…”
Section: Discussionsupporting
confidence: 88%
“…Activation also includes change of the angle between the N and C domains of β-arrestin-2 (74, 75). Additionally, the C-edge loops of arrestins can act as a membrane anchor to stabilize the PAR1-β-arrestin complex (77). Activated β-arrestin-2 can have different conformations, which in part are mediated by phosphorylation of at least six residues including Thr178, Ser194, Ser267, Ser268, Ser281, Ser361 and Thr383 (76).…”
Section: The Model Of Apc-mediated Par1 Biased Signaling Complexmentioning
confidence: 99%
“…Along with their signaling functions, β-arrestins are able to modulate the interaction of GPCRs with different types of G-proteins, as was shown for type 1 parathyroid hormone receptor (PTH1R) coupled to both Gs-and Gq/11proteins [29]. It is important to point out that the functions of different types of arrestins, β1 and β2, in parathyroid hormone-induced signaling differ significantly, which is due to differences in their conformations when binding to an activated PTH1R [29].…”
Section: Introductionmentioning
confidence: 96%
“…Being in the "tail" conformation, β-arrestins preferentially interact with the intracellular C-terminal domain of GPCR, which is phosphorylated by specific G protein-coupled receptor kinases (GRKs), while in the "core" conformation they are capable of interact with the transmembrane domain (TMD) of the receptor [25][26][27][28]. Along with their signaling functions, β-arrestins are able to modulate the interaction of GPCRs with different types of G-proteins, as was shown for type 1 parathyroid hormone receptor (PTH1R) coupled to both Gs-and Gq/11proteins [29]. It is important to point out that the functions of different types of arrestins, β1 and β2, in parathyroid hormone-induced signaling differ significantly, which is due to differences in their conformations when binding to an activated PTH1R [29].…”
Section: Introductionmentioning
confidence: 99%